Illegal actions in the field of bankruptcy: conceptual and comparative law aspects - Oliynychuk, Oleksandra; Ronska, Olha (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
The article is devoted to the issues of illegal actions in bankruptcy. The aim of the article is to study the conceptual and comparative law aspects of illegal actions in the field of bankruptcy. This article outlines the destructive impact of bankruptcy for selfish motives on the economy. Deliberately bankrupting a business entity is contrary to market laws, worsens the business climate in the country, and undermines investor confidence. Such situations often do not have local consequences, but can have a negative impact on the economy of the industry and / or region and the country as a whole. Violations of bankruptcy requirements are considered, namely: “fictitious bankruptcy”, “concealment of bankruptcy”, “making bankrupt”. A comparison of the content of definitions of their concepts and differentiation by a number of criteria. It is concluded that all concepts refer to acts of illegal nature in bankruptcy proceedings, which are a deviation from good economic practice; in all types of illegal actions related to bankruptcy, there is emphasis on “great material damage” to creditors or the state; “fictitious bankruptcy” and “making bankrupt” are somewhat opposed in their content to “concealment of bankruptcy”; “fictitious bankruptcy” and “concealment of bankruptcy” in accordance with current legislation are administrative offenses, while “making bankrupt” is a criminal offense; in all three cases, a fine is provided, and in the event of making bankrupt, the penalty is accompanied by deprivation of the right to hold certain positions or engage in certain activities for up to three years. It is reasonably stated that there are significant difficulties in proving the fact of making bankrupt of a business entity. The data of the Unified State Register of Judgments in this category of cases were studied and it was established that during the period from 01.01.2012 to 01.01.2022 no verdict was passed. The conclusion is made about the expediency of decriminalization of making bankrupt and transfer of this offense to the administrative legal and economic legal planes.